Near‐Infrared‐Light Remote‐Controlled Activation of Cancer Immunotherapy Using Photothermal Conjugated Polymer Nanoparticles. Issue 34 (18th July 2021) - Fu, Xuancheng; Huang, Yiming; Zhao, Hao; Zhang, Endong; Shen, Qi; Di, Yufei; Lv, Fengting; Liu, Libing; Wang, Shu
Abstract: Remote control of the therapeutic process is an ideal strategy for maximizing efficacy and avoiding side effects, especially for cancer immunotherapy. Herein, a conjugated polymer nanoparticles (CPNs)‐mediated optogenetic system for in situ activation of immunotherapy under near‐infrared laser irradiation is reported. This system is composed of photothermal CPNs and interferon‐gamma (IFN‐γ) plasmid driven by heat shock promoter HSP70. The photothermally responsive CPNs serve as a photo–heat nanotransducer to trigger the gene transcription of IFN‐γ cytokine. The secreted IFN‐γ from cancer cells can sufficiently elicit surrounding tumor‐associated macrophages activation through IFN‐γ‐JAK‐STAT1 transcription‐factor signaling pathway and finally induce cancer cell killing by immunotherapy. Therefore, this synergetic optogenetic system provides a promising approach to remotely control the process of cancer immunotherapy. Abstract : A new strategy for near‐infrared‐light remote‐controlled activation of cancer immunotherapy is developed using photothermal conjugated polymer nanoparticles (CPNs). The CPNs serve as a photo–heat nanotransducer to trigger the gene transcription of the IFN‐γ cytokine. The secreted IFN‐γ can sufficiently elicit surrounding tumor‐associated macrophages activation followed by cancer cell killing by immunotherapy.